2001
DOI: 10.1097/00005537-200108000-00011
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Differences in Mucoepidermoid Carcinoma and Adenoid Cystic Carcinoma of the Major Salivary Glands

Abstract: There is a clear difference in the molecular phenotypes of MEC and ACC. The lack of statistically significant expression in ACC, when compared with similar uninvolved salivary gland tissue, suggests minimal involvement for these molecular structures in the pathogenesis of ACC. Conversely, erbB-2, erbB-3, EGFR, and TGF-alpha may have a role in the development and progression of MEC. These results have therapeutic implications for MEC of the major salivary glands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
53
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 31 publications
(36 reference statements)
6
53
0
3
Order By: Relevance
“…The overexpression of EGFR is generally believed to be common in salivary gland carcinoma, although the incidence of positive EGFR staining was found to be 25% (2/8) in an earlier study with a small sample size (20). Gibbons et al found 17 out of 22 (77%) mucoepidermoid carcinoma cases with EGFR overexpression (21). We reported on a series of 46 patients of mucoepidermoid carcinoma.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…The overexpression of EGFR is generally believed to be common in salivary gland carcinoma, although the incidence of positive EGFR staining was found to be 25% (2/8) in an earlier study with a small sample size (20). Gibbons et al found 17 out of 22 (77%) mucoepidermoid carcinoma cases with EGFR overexpression (21). We reported on a series of 46 patients of mucoepidermoid carcinoma.…”
Section: Discussionmentioning
confidence: 71%
“…According to the limited literature, the overexpression of EGFR was reported to be 25 and 77% respectively (20,21). EGFR-targeted drugs are now commercially available, including small-molecule tyrosine kinase inhibitors (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neuroendocrine tumors of the lung, including small cell carcinomas, usually do not express EGFR 13 and are virtually always negative for EGFR mutation. 14 Although EGFR expression has been reported in salivary gland carcinomas of the head and neck, [15][16][17][18] little is known about EGFR mutation, amplification, and expression in salivary gland-type tumors of the lung.…”
mentioning
confidence: 99%
“…There have been suggestions that the overexpression of c-erbB-2 on salivary gland tumors is related with histogenesis of these lesions (Glisson et al, 2004;Rivière et al, 1991;Gibbons et al, 2001, Rosa et al, 1997. MEC is composed of varying proportions of mucous, epidermoid, columnar, intermediate and clear cells (Auclair et al) and is though to arise from the salivary excretory duct (Ellis et al).…”
Section: Discussionmentioning
confidence: 99%